Experimental study of the conventional equation to determine a plate's moment of inertia - Pintao, CAF; de Souza, M. P.; Grandini, Carlos Roberto [UNESP]; Hessel, R. (Iop Publishing Ltd, 2004)
In this work, we describe an experimental setup in which an electric current is used to determine the angular velocity attained by a plate rotating around a shaft in response to a torque applied for a given period. Based on this information, we show how the moment of inertia of a plate can be determined using a procedure that differs considerably from the ones most commonly used, which generally involve time measurements. Some experimental results are also presented which allow one to determine parameters such as the exponents and constant of the conventional equation of a plate's moment of inertia.